Management and Cost Analysis of Insurance-Based Social Benefits in the Republic of Azerbaijan - Alirzayev, Emin (Dr. Viktor Koval, 2025)
Introduction. Mechanisms for strengthening social protection in the Republic of Azerbaijan are important to improve social payments within the state’s social insurance (insurance-pension) system. The relevance lies in establishing a theoretical and conceptual framework for making informed decisions on improvements at the management level based on the optimal use of the state social insurance system’s financial and resource capabilities for social protection. Aim and tasks. This study aims to substantiate management decisions and analyse the cost of social protection within the current state of the social insurance system in Azerbaijan. The study also analyses the importance of implementing this benefit scheme in the Republic of Azerbaijan, its role in social protection, and the need to increase its amount. Results. The analysis of social protection costs within Azerbaijan's current state social insurance system highlights the need to increase childcare benefits by 57.1% for children under 1.5 years of age and 59.1% for children aged 1.5 to 3 years. This need is driven by demographic changes (from 5.2 children per woman in the 1970s to 1.825 in the 2020s), increasing life expectancy (from 69.8 years in the 1970s to 76 years in 2023), and a shrinking working-age population (the share of children aged 0-14 years fell from 32.6% in 1995 to 21.2% in 2024). This trans poses long-term risks to the pension system's financial sustainability and social protection. Currently, the benefit is only 16.29% of the subsistence minimum and less than 3.5% of the monthly food expenses, which is insufficient for the needs of families. The State Social Protection Fund (hereinafter – Fund) has sufficient resources for an increase, which is confirmed by the analysis of the budget and the dynamics of income from mandatory contributions. The share of childcare benefits in the fund's total expenses is only 0.14%, and its share in GDP is less than 0.01%. International experience confirms that increasing benefits can increase birth rates and reduce poverty. Conclusions. This study strengthens the foundation for making prospective socio-economically effective decisions in the field of social protection based on a grounded approach, as well as international experience. Currently, there are unused economic and financial opportunities to revise (increase) the amount of childcare benefits that are of public interest in the Republic of Azerbaijan. Moreover, sufficient motives exist for introducing these increases, which would be acceptable as management tools for improvement.